Giant U Wave: Tanda Bahaya yang Harus Dikenali dalam Praktik Klinik Primer - Asrina Enggarela (Cermin Dunia Kedokteran, 2023)
Introduction:  Detection of hypokalaemia by ECG accompanied by detailed history and physical examination will greatly facilitate diagnosis, initiate potassium correction therapy, and prevent further complications due to various cardiac arrhythmias and neurological dysfunctions. Case: A 40-year-old man with weakness in both leg muscles since last night, starting from the legs up to the thighs. Initial ECG showed sinus rhythm with a heart rate at 80 bpm, first-degree heart block (PR interval 240 ms); Q wave in III lead; “apparent” prolonged QTc interval at 551 ms; ST segment depression in I, II, and V3-V6 leads; ST segment elevation in aVR lead; T-wave inseparable from large U wave formed giant U wave that remarkedly seen in V2-V4 leads. Laboratory tests revealed very low serum potassium at 1.94 mmol/L Conclusion: In severe hypokalaemia, T and U waves will merge and form a giant U wave. Emergency and primary physicians should be familiar with the ECG changes of hypokalaemia, especially the giant U wave.